Performative reflections: through the lens of José Ortiz Echagüe - Pomés Jiménez, Beatriz; Hermans, Sef; Saenz Abarzuza, Igor; Macdevitt, Patrick (Dykinson, 2024)
The Museum University of Navarra (MUN) is home to the vast photographic output of José Ortiz Echagüe. Bequeathed to the University of Navarra in 1990, the collection led to the creation of a permanent exhibition space at the MUN in 2007. Since then, the photographs of Ortiz Echagüe have directly influenced and inspired many other artistic initiatives held at the Museum, with specific impact in contemporary dance. This article reflects on the connections between the photographic output of José Ortiz Echagüe and four dance productions. How do these photographs act as visual triggers for contemporary choreographers and creators? How do still images inspire movement and other elements of scenography? What are the creative processes involved in devis- ing movement to a bidimensional work of art? How does photography turn into per- formance art? How can these portrayals of 20th Century Spain be translated to our present? The goal of this chapter is threefold. On one hand, it aims to highlight the relevance of Ortiz Echagüe’s photographs at present, the timelessness of his portrayal of Spanish identity, and the relevance of this archive for modern-day creative productions in the art. On the other hand, it contributes to outlining the creative processes related to the creation of a photography-based dance production. Finally, this article will also act as an academic framework for a future artistic collaboration between the MUN and Farout, a Creative and Performative Artistic Research Collective.
Capítulo del libro: Guidobono, S. O. (2021). El devenir de las civilizaciones: interacciones entre el entorno humano, natural y cultural. Dykinson.
Keywords: performance; dance; photography; creativity; creative processes; José Ortiz Echagüe